Paradigm Shift in a Multilinguistic Context: Constructing National Identity and Socio-Religious Harmony in Cameroon Urban Music - Fai, Gilbert Tarka; Vernyuy, Lawir Blessing (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
Cameroon, often described as